1
$\begingroup$

So I have got the following equation: $$x\frac{\partial u}{\partial x} - 2 \frac{\partial u}{\partial y} = 2u$$

I have tried to solve the following way. I was taught that LHS can be thought of as the directional derivative of $u$ in the direction of the vector $\begin{bmatrix}x \\ -2\end{bmatrix}$. Therefore, on the curves defined by $$\frac{dy}{dx} = \frac{-2}{x} ==> y = - 2ln(x) + K$$ the PDE reduces to an ODE of the form: $$\frac{du}{dx} = 2u ==> u = e^{2x}e^K$$ where $k$ is a constant. Therefore $u(x,y)$ must be: $$ e^{2x} f(y + 2ln(x))$$ where $f$ is any arbitrary function. However this solution is wrong (I have plugged in the equation and checked with Maple).

$\endgroup$
  • 1
    $\begingroup$ I upvoted your question for the efforts you have shown $\endgroup$ – Isham May 13 '18 at 20:14
2
$\begingroup$

This line is not correct $$\frac{du}{dx} = 2u ==> u = e^{2x}e^K$$ It should be $$\frac{du}{2u} = \frac {dx}x \implies ..... $$

Here is my approach

$$x\frac{\partial u}{\partial x} - 2 \frac{\partial u}{\partial y} = 2u$$ Lagrange equation is $$\frac {dx}{x}=-\frac {dy}{2}=\frac {dz}{2z}$$ Integrating first equation $$ \int \frac {dx}{x}=-\frac 12 dy \implies \ln(x)=-\frac 12y +C_1$$ $$\implies C_1=\ln(x)+\frac 12y$$ Integrating second eqaution $$-\frac {dy}{2}=\frac {dz}{2z} \implies \ln(z)=-y+C_2$$ $$\implies C_2=\ln(z)+y$$ Therefore $$\ln(z)+y=f(\ln(x)+\frac12y)$$ $$\ln(z)=f(\ln(x)+\frac12y)-y$$ $$\displaystyle u=\displaystyle e^{f(\ln(x)+\frac12y)-y}$$ $$\displaystyle \boxed{u(x,y)=\displaystyle F(\ln(x)+y/2)e^{-y}}$$

$\endgroup$
  • 1
    $\begingroup$ It's worth pointing out that $e^{f(\ln x + y/2)} = F(\ln x + y/2)$ $\endgroup$ – Dylan May 13 '18 at 18:50
  • $\begingroup$ That's really helpful, however I am struggling to understand why approach went wrong. $\endgroup$ – daljit97 May 13 '18 at 18:58
  • 1
    $\begingroup$ @daljit97 : Your claim that $\frac{du}{dx}=2u$ is wrong, the right side has to be the fraction $\frac{2u}{x}$. $\endgroup$ – LutzL May 13 '18 at 19:02
  • 2
    $\begingroup$ @daljit97 : Your solution is a surface with 2 free parameters. If you decompose it into characteristic curves, you get a one-parameter family. Thus the 2 integration constants, which are constants along characteristic curves, have to be dependent. $\endgroup$ – LutzL May 13 '18 at 20:09
  • 1
    $\begingroup$ @LutzL oh alright that makes sense $\endgroup$ – daljit97 May 13 '18 at 20:11
1
$\begingroup$

On the curves with $y=-2\ln(x)+K_1$ the derivative of $z(x)=u(x,-2\ln(x)+K_1)$ is $$ z'(x)=u_x-\frac2xu_y=\frac2xz(x) $$ which has the solution $z=K_2x^2$ and with $K_2=f(K_1)$ the general solution form is $$ u(x,y)=x^2f(2\ln(x)+y) $$ so that you get a slightly different factor.


Note that the first identity can also be written as $x^2e^y=C$ so that then the alternative form of the general solution is $$ u(x,y)=x^2g(x^2e^y)=e^{-y}h(x^2e^y). $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.